The Effect of Radical Prostatectomy, External Beam Radiation Therapy and Active Surveillance on Life Insurance Premiums in Patients with Prostate Cancer. Issue 5 (September 2017) - Piecuch, Michael; Biebel, Mark; Stock, Jeffrey; George, Hank; Wright, Christopher
Abstract : Introduction: : Patients with early stage, low risk prostate cancer are typically treated with radical prostatectomy, external beam radiation therapy or active surveillance. We examine how these different management options affect life insurance underwriting practices. Methods: : A total of 20 life insurance companies were sent questionnaires with 9 sample patient cases. Patients were diagnosed with low risk prostate cancer at age 55, 65 or 75 years, and treated with radical prostatectomy, external beam radiation therapy or active surveillance. The life insurance companies were then asked what their underwriting decision would be (standard, substandard or decline) for each sample patient if he submitted a 500, 000 term life insurance application at 1, 3 and 5 years after treatment initiation with no evidence of disease on followup. Results: : Of the 20 life insurance companies 12 (60%) responded to the questionnaire. In all age groups standard life insurance premiums were most likely to be granted after radical prostatectomy (52.7%), followed by external beam radiation therapy (36.0%) and lastly by active surveillance (5.6%). Regardless of management option, standard premiums were also more likely to be granted if prostate cancer was diagnosed at an older patient age and if there had been a longer duration of disease‐free followup (54.6% after 5 years vs 31.0% after 1 year). Conclusions: : For patients diagnosed with low risk prostate cancer life insurance companies are more likely to grant standard life insurance premiums after radical prostatectomy or external beam radiation therapy rather than active surveillance. Other predictors of favorable underwriting decisions are older age at diagnosis as well as longer duration of disease‐free followup.